Pleural metastasis detected by transesophageal endoscopic ultrasonography. Issue 5 (8th February 2019) - Rana, Surinder S; Gupta, Parikshaa; Sharma, Ravi K; Gupta, Rajesh
Abstract : Patients with pleural effusion and inconclusive repeated pleural fluid biochemical and cytological analysis are a diagnostic dilemma that is usually solved by invasive procedures such as diagnostic thoracoscopy. We report a 62‐year‐old male with malignant pleural effusion as well as ascites who was diagnosed using endoscopic ultrasound‐guided fine‐needle aspiration of pleural deposit. We also report contrast enhanced endoscopic ultrasound findings of pleural deposits. Abstract : In some patients, repeated ascitic or pleural fluid analysis is inconclusive for underlying etiology. In these patients, endoscopic ultrasound can help in visualizing as well as sampling the pleural or peritoneal deposits.